Estimating changes in hydration status from changes in body mass: Considerations regarding metabolic water and glycogen storage - King, R. F. G. J.; Cooke, C.; Carroll, S.; O'Hara, J. (Journal of Sports Sciences, 2008)
The potential for imprecision in the estimation of hydration status from changes in body mass has been outlined previously but the equations derived from these derivations appear inconsistent. Reconciliation of body mass loss in terms of sweat loss and effective body water loss is possible from specific equation sets provided that gains and losses of both body mass and water used in the derivation of sweat loss and to derive effective body water loss are in inclusive equation sets. This is obligatory so that mass and water changes as quantifiable determinants are consistent with both internal processes and external gains and losses. Thus, body mass loss, substrate oxidation, metabolic water, and all the terms used in simultaneous equation sets have to be reconciled not only as identical variables but mathematically balance exactly. The revised equation for effective body water loss given here is different from that originally proposed. Metabolic water is part of body mass loss corrected for substrate oxidation, fluid ingestion, and respiratory water to derive sweat loss and it may not be justified to also include water associated with glycogen as releasable bound water. Accordingly, our calculated effective body water loss is substantially a greater loss than originally supposed but clearly still less than the simple balance between mass loss and fluid ingested.